Rešitve za e-sodstvo, ki bo v pomoč, ne v breme - Horvat, Vladimir (Podjetje in delo, 2013)
The article presents the state of computerization in judiciary in the Republic of Slovenia and its future development. It also presents the organization structure behind the computerization of judicial proceedings, the goals, the strategy, and the development principles of the computerization. The author emphasizes that the discoursive level by itself does not guarantee desired reality. He is critical about reasons hampering more effective development and he warns about lengthy public procurement proceedings for developing the electronic applications and the lack of the expert IT personnel being the foundation for computerized court registries and judicial proceedings. The author also presents the starting points for elimination of obstacles which deter higher level of user friendliness of electronic applications. He especially presents e-register which is in his opinion the heart and engine of such computerization which will be of assistance and will not present a burden. The author draws attention to moral-ethic dimension of judicial decision-making which ought to have the computerization as its indispensable servant.
Keywords: elektronsko poslovanje; pravosodje; sodišča; sodni postopek